Performing Islam : gender and ritual in Iran - Torab, Azam. (Women and gender, the Middle East and the Islamic world,, 2007)
Performing Islam takes as its main focus the rich array of ceremonial activities that shape and inform the lives of circles of women in south Tehran. Based on anthropological fieldwork, the book describes and analyses rituals that mark religious anniversaries and life course events in Iran today. Arguing that the ritual performances are powerful forums where ideas develop, and where rules, symbols and discourses are contested, this book discusses the values and beliefs underpinning gender constructions in a rapidly changing and complex society. The ambiguous metaphorical language of the rituals is examined, revealing how gender ideologies are projected and renewed, but also challenged, destabilized and ridiculed. Thus the rituals provide possibilities for self-expression, innovation and incremental change. This study goes beyond questions of meaning and culture to interrogate the dynamics of gender performance as products of power and politics.